Heterotaxy Syndrome and Spectrum of Cardiac Involvement - Munesh Tomar; Maitri Chaudhuri (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
Heterotaxy syndrome, a birth defect characterized by abnormal arrangement of organs, is strongly associated with complex congenital heart disease (CHD). This syndrome, which arises from disruptions in early embryonic development, particularly in the establishment of left-right asymmetry, leads to a range of cardiac and extracardiac malformations. The severity of CHD in heterotaxy can vary, and individuals may experience both intra- and extracardiac anomalies. Here in this review article, we are discussing various aspects of cardiac involvement in heterotaxy syndrome and role of imaging modalities.